2010
DOI: 10.1038/ismej.2010.186
|View full text |Cite
|
Sign up to set email alerts
|

A novel clade of Prochlorococcus found in high nutrient low chlorophyll waters in the South and Equatorial Pacific Ocean

Abstract: A novel high-light (HL)-adapted Prochlorococcus clade was discovered in high nutrient and low chlorophyll (HNLC) waters in the South Pacific Ocean by phylogenetic analyses of 16S ribosomal RNA (rRNA) and 16S-23S internal transcribed spacer (ITS) sequences. This clade, named HNLC fell within the HL-adapted Prochlorococcus clade with sequences above 99% similarity to one another, and was divided into two subclades, HNLC1 and HNLC2. The distribution of the whole HNLC clade in a northwest to southeast transect in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
50
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 38 publications
9
50
1
Order By: Relevance
“…In contrast, the single-cell approach described here provides unequivocal linkages among functional genes, 16S rRNA and ribosomal ITS sequences. Thus, we were able to compare our single cells with the gene sequences of the previous studies and determine if the functional genes identified by Rusch et al (2010) are associated with the 16S rRNA sequences identified by West et al (2011). Phylogenetic analyses confirm the same novel clades of Prochlorococcus were identified independently in all three cases (Figure 2).…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…In contrast, the single-cell approach described here provides unequivocal linkages among functional genes, 16S rRNA and ribosomal ITS sequences. Thus, we were able to compare our single cells with the gene sequences of the previous studies and determine if the functional genes identified by Rusch et al (2010) are associated with the 16S rRNA sequences identified by West et al (2011). Phylogenetic analyses confirm the same novel clades of Prochlorococcus were identified independently in all three cases (Figure 2).…”
Section: Resultssupporting
confidence: 55%
“…However, it was unclear whether these previously described clades are the same as connections could not be made between the core functional genes reported by Rusch et al (2010) and the 16S rRNA sequences reported in West et al (2011). The partial genomes assembled de novo by Rusch et al (2010) from metagenomic sequences were not suitable for phylogenetic analysis because the genomes, and the genes comprising them, were composites derived from multiple organisms.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations